Metal concentration in commonly sold fruit vegetables in dhaka city market and probable health risk (Dhaka University Journal of Biological Sciences, 2021)
The present study evaluated the concentration of heavy metals in six different fruit vegetables collected from Kawran Bazar market of Dhaka city of Bangladesh. The analyzed fruit vegetable samples were randomly collected, processed and analyzed for heavy metal determination using atomic absorption spectrophotometry (AAS). Mean concentrations (mg kg-1) of Cr, Cd, Pb, Ni, Cu, Zn, Fe and Mn of Lady’s finger, Pumpkin, Tomato, Brinjal, Snake gourd and Cucumber were within the range of 0.83 to 4.88, 0.08 to 0.18, 0 to 3.00, 0.33 to 3.70, 8.10 to 10.88, 17.81 to 45.91, 53.00 to 131.50 and 10.40 to 45.90 mg kg-1 of dry weight, respectively. Mean concentration (mg kg-1) of Cr in Brinjal (4.88); Pb in Pumpkin (3.00) and Brinjal (0.50); Ni in Snake gourd (3.70); Cu in Lady’s finger (10.10), Brinjal (10.88), Snake gourd (10.53) and Cucumber (10.48) were higher than the maximum permissible limit (MPL). The study suggests regular monitoring of heavy metals in vegetables to prevent excessive accumulation in human body.Dhaka Univ. J. Biol. Sci. 30(1): 35-47, 2021 (January)